Forecasting the Number of Foreign Tourists Who Visit to East Java Using Monte Carlo Method - Syariful Alam; Syariful Alim (Fakultas Teknik Universitas Bhayangkara, 2018)
Indonesia has many islands and there are beautiful inland areas, interesting historical and cultural ruins,beaches, mountains, and more. Especially in the tourism sector is one of the largest industries that are veryinfluential and grow very fast. The advancement of the tourism industry in a region is very dependent on thenumber of tourists who come both domestic and foreign tourists. The large number of foreign tourists that comepush and accelerate economic growth. So that directly leads to an increase in demand for goods and services. Tomeet the needs and demands of tourists, it is necessary to predict the number of visits of foreign tourists. Onemethod that can be used in forecasting is Monte Carlo. From the results of Monte Carlo research can work well,From the stage of the prediction system implementation that has been built using the initial parameter 12 months100x simulation and delta-t = 0.001, then get sigma = 52.2650054, Mu = -0.0398. And the simulation is moreaccurate in predicting the number of foreign tourist visits in East Java, which has a small error value. To get asmaller error value is by reducing or delta-t value.